PENGARUH LATIHAN VARIASI TENDANGAN TERHADAP KETEPATAN SHOOTING PADA TIM SEPAKBOLA SMAN 2 TANAH PUTIH - Zulfikar Zulfikar; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted to find out whether there is influence ofvariation of Kick against Shooting on Football Team SMAN 2 Tanah Putih, when doingcounter attack for lack of variation of kicking kicks so many attacks are wasted. Theform of this research is experimental (Experimental) research, with the soccer playerpopulation of SMAN 2 Tanah Putih, the data in this study is the entire population of 15people. The instrument performed in this study is a Test Shoot the ball to the target,which aims to measure the accuracy of the kick into the goal. After that, the data wereprocessed by statistics, to test the normality by lilifors test at a significant level of α(0.05). The hypothesis proposed is the effect of variation of kick exercises on theprecision of Shooting on Football team SMAN 2 Tanah Putih, Based on t test analysisyield T count equal to 3.57 and T table 0,227, mean T count> T table. Based onstatistical data analysis, there is average pree-test of 4.20 and average post-test of 5.15,then the data is normal. Thus, there is an Effect of Kick Variations Exercise on theprecision of Shooting on the Football team of SMAN 2 Tanah Putih.Keywords: Kick variations, Shooting Accuracy